2016
DOI: 10.15171/ijb.1287
|View full text |Cite
|
Sign up to set email alerts
|

VIT-CMJ2: Endophyte of Agaricus bisporus in Production of Bioactive Compounds

Abstract: Background:Agaricus bisporus is an edible basidiomycete fungus. Both the body and the mycelium contain compounds comprising a wide range of antimicrobial molecules, contributing in improvement of immunity and tumor-retardation. Objectives: The presence of endophytes capable of producing bioactive compounds was investigated in Agaricus bisporus. Materials and Methods: Endophytes from Agaricus bisporus was isolated on LB agar. The obtained isolates were characterized morphologically and biochemically. Further 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Mantovani et al 17 reported that only after two-year cryopreservation it is possible to verify the effect of long-term preservation on mycelial viability maintenance. Moreover, the long-term cryopreservation could affect not only the mycelial cell survival but also other microorganisms inside the mycelia such as endosymbionts, similar to endophytes, 31 which could interfere with mycelial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Mantovani et al 17 reported that only after two-year cryopreservation it is possible to verify the effect of long-term preservation on mycelial viability maintenance. Moreover, the long-term cryopreservation could affect not only the mycelial cell survival but also other microorganisms inside the mycelia such as endosymbionts, similar to endophytes, 31 which could interfere with mycelial growth.…”
Section: Discussionmentioning
confidence: 99%
“…By the neighbor-joining tree technique, the phylogenetic tree was built. The consensus sequences were deposited in GenBank (Gautam et al, 2016(Gautam et al, ). 10.3389/fmicb.2024 Frontiers in Microbiology 04 frontiersin.org…”
Section: Molecular Genomic Recognition Of Endophytic Fungusmentioning
confidence: 99%
“…Turbo mass software (5.4.2 version) was used for the spectrum analysis. The configurations of the chemical were compared to the mass spectral outlines in the NIST collection (2008) (Gautam et al, 2016).…”
Section: Gc-ms Analysis Of Pts8 Fungal Crude Extractmentioning
confidence: 99%
“…Endophytes were isolated according to the method described by Gautam et al (2016) with slight variations. To isolate the endophytic bacteria, the surface of the mushroom was sterilized with 4% sodium hypochlorite solution, 70% ethyl alcohol, and sterile double-distilled water (ddH 2 O).…”
Section: Isolation Of Endophytic Bacteriamentioning
confidence: 99%